Early Liver and Kidney Dysfunction Associated with Occupational Exposure to Sub-Threshold Limit Value Levels of Benzene, Toluene, and Xylenes in Unleaded Petrol - Masoud Neghab; Kiamars Hosseinzadeh; Jafar Hassanzadeh (Elsevier, 2015)
Background: Unleaded petrol contains significant amounts of monocyclic aromatic hydrocarbons such as benzene, toluene, and xylenes (BTX). Toxic responses following occupational exposure to unleaded petrol have been evaluated only in limited studies. The main purpose of this study was to ascertain whether (or not) exposure to unleaded petrol, under normal working conditions, is associated with any hepatotoxic or nephrotoxic response. Methods: This was a cross-sectional study in which 200 employees of Shiraz petrol stations with current exposure to unleaded petrol, as well as 200 unexposed employees, were investigated. Atmospheric concentrations of BTX were measured using standard methods. Additionally, urine and fasting blood samples were taken from individuals for urinalysis and routine biochemical tests of kidney and liver function. Results: The geometric means of airborne concentrations of BTX were found to be 0.8 mg m−3, 1.4 mg m−3, and 2.8 mg m−3, respectively. Additionally, means of direct bilirubin, alanine aminotransferase, aspartate aminotransferase, blood urea and plasma creatinine were significantly higher in exposed individuals than in unexposed employees. Conversely, serum albumin, total protein, and serum concentrations of calcium and sodium were significantly lower in petrol station workers than in their unexposed counterparts. Conclusion: The average exposure of petrol station workers to BTX did not exceed the current threshold limit values (TLVs) for these chemicals. However, evidence of subtle, subclinical and prepathologic early liver and kidney dysfunction was evident in exposed individuals.